Kelimpahan Bakteri Vibrio sp. pada Air Pembesaran Udang Vannamei (Litopenaeus vannamei) sebagai Deteksi Dini Serangan Penyakit Vibriosis [The Abundance Of Vibrio sp. Bacteria On Enlargement Water Of Litopenaeus vannamei As The Early Detection Of Vibriosis] - Abdul Manan; Adnan Kharisma (Jurnal Ilmiah Perikanan dan Kelautan, 2012)
Abstract The abundance of bacteria is an activity that aims to determine the distribution and the abundance of bacteria in a water area, so an effort to control and prevent against these bacteria can be made to avoid it's wide spread. The function of this monitoring activities is for an early detection of animal health conditions that is the white leg shrimp due to bacterial attack. Given the importance of health level in the cultivation of white leg shrimp, then the monitoring activity in bacterial abundance should be done because the number of bacteria found in aquatic environments shouldn't exceed the minimum threshold number of bacteria that is 104 CFU/ml. The purpose of this study case is to know the abundance of Vibrio sp. on white leg shrimp water augmentation. Because the Vibrio sp. bacteria is known as the opportunistic pathogen of white leg shrimp, which can cause disease if the environmental conditions are bad. Working methods used is descriptive method of data collection techniques include primary and secondary data. The stage of the monitoring activity include: (1) Preparation phase which includes the preparation of equipment and materials and sterilization equipment and media. (2) Phase of making trisalt solvent and bacterial culture media. (3) Phase of retrieval and delivery the water samples. (4) Phase planting the water samples. (5) Phase counting the bacteria. (6) Interpretation the results of the calculation. Based on the results of monitoring the abundance of bacteria in white leg shrimp water augmentation activity, the conclusion is the abundance of Vibrio sp. on white leg shrimp water augmentation has exceeds the minimum threshold number of bacteria that is 104 CFU/ml, so the white leg shrimp culture is susceptible againts these Vibriosis disease.